ANALISIS KERUSAKAN JALAN DATUK SETIA MAHARAJA PEKANBARU DENGAN METODE PAVEMENT CONDITION INDEX (PCI) - Elianora Elianora; Horas Saut.M.M; Ere Zij Sheagle S (Jurnal TeKLA, 2021)
Datuk Setia Maharaja Street Pekanbaru is a collector road connecting between the activity centers of Pekanbaru city and has a length of 1,620 meters and a width of 12 meters. There are several damages that make it uncomfortable for motorists who pass through the road so that repairs are needed. The purpose of this study was to determine the types of road damage and determine the index value of the flexible pavement condition using the Pavement Condition Index (PCI) method. The research was conducted into 8 segments with a size of 200 meters per segment. The results of the analysis showed that the damage to Datuk Setia Maharaja street Pekanbaru  included subsidence, lumps, obesity, potholes, grain release, block cracks, crocodile skin cracks, diagonal cracks, transverse cracks, longitudinal cracks, edge cracks, slip cracks, burrs, and fillings. The average PCI score is 54 with Fair conditions. This shows that a serious response from the government is needed to immediately make repairs before the damage becomes more severe.